2023
DOI: 10.1111/jerd.13009
|View full text |Cite
|
Sign up to set email alerts
|

Color stability of resin‐based composites exposed to smoke. A systematic review

Abstract: Objective: To conduct a systematic review on color stability of dental resin-based composites (RBC) exposed to conventional and electronic cigarettes. Materials and Methods: In vitro studies reporting on the color stability of RBC exposed to conventional cigarettes or to e-cigarettes: both Tobacco Heating Systems (THS) and Electronic Nicotine Delivery Systems (ENDS). The quality of the included studies was assessed with the QUIN tool (risk-of-bias tool for assessing in vitro studies conducted in dentistry). A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 57 publications
0
10
0
Order By: Relevance
“…In addition to providing improved mechanical properties, the restorations performed with these materials should simulate aesthetic characteristics, such as surface smoothness, color, translucency, and gloss of dental tissue, and maintain stability over time [ 27 ]. RBCs are in fact subject to exposure to extrinsic and intrinsic coloring agents that can influence color stability and translucency over time [ 1 , 9 ]. In the present study, significant differences were reported for ΔE 00 , TP, and CR values after staining (T1), leading to the conclusions that the investigated staining procedures significantly influences color and translucency.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to providing improved mechanical properties, the restorations performed with these materials should simulate aesthetic characteristics, such as surface smoothness, color, translucency, and gloss of dental tissue, and maintain stability over time [ 27 ]. RBCs are in fact subject to exposure to extrinsic and intrinsic coloring agents that can influence color stability and translucency over time [ 1 , 9 ]. In the present study, significant differences were reported for ΔE 00 , TP, and CR values after staining (T1), leading to the conclusions that the investigated staining procedures significantly influences color and translucency.…”
Section: Discussionmentioning
confidence: 99%
“…In many papers investigating color stability, staining procedures are generally performed by a simple static immersion of RBC specimens in staining media [ 1 ]. Few papers have used more complex in vitro simulations including specific temperatures, cycling between staining and neutral solutions (water or artificial saliva) [ 8 ], smoking [ 9 , 10 , 11 ], pH variations [ 3 ], or tooth brushing simulation [ 12 , 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Resin composite restorations are subjected to different types of stains in the oral cavity [ 15 , 16 ]. Discoloration is generally divided into internal and external discoloration; internal discoloration of resin composites is produced by physical and chemical reactions in the innermost layers of the resin composite, while the external discoloration mainly arises from consumption of coloring agents from different sources, such as food, beverages, smoking, and frequent application of mouthwashes [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Red wines were shown to result in increased surface roughness and erosion of nanohybrid and nanofilled resin composites, as compared to white wines, due to their higher alcohol concentration [ 22 ]. In addition a recent systematic review by Paolone et al [ 23 ] reported that cigarette smoke, whether conventional or electronic cigarettes, significantly affect the color stability of resin composites. Cigarette smoke was also reported to affect the surface roughness of various dental resin composites materials [ 24 – 27 ].…”
Section: Introductionmentioning
confidence: 99%